Bariatric surgery and obesity: influence on the incretins - Laferrère, B (Int J Obes Suppl, 2016)
The gut hormone incretins have an important physiological role in meal-related insulin release and post-prandial glucose control. In addition to weight loss, the incretin hormones have a role in glucose control after bariatric surgery. The release of incretins, and specifically of glucagon-like peptide (GLP)-1, in response to the ingestion of nutrients, is greatly enhanced after gastric bypass (RYGBP). The rapid transit of food from the gastric pouch to the distal ileum is responsible for the greater GLP-1 release after RYGBP. The incretin effect on insulin secretion, or the greater insulin response to oral glucose compared to an isoglycemic intravenous glucose challenge, is severely impaired in patients with type 2 diabetes, but is recovered rapidly after RYGBP. The improvement in insulin secretion rate and β-cell sensitivity to oral glucose after RYGBP is mediated by endogenous GLP-1, and is abolished by exendin 9–39, a specific GLP-1 receptor antagonist. While calorie restriction and weight loss have major effects on the rapid and sustained improvement of fasted glucose metabolism, the enhanced incretin effect is a key player in post-prandial glucose control after RYGBP.